Barkar det åt skogen för svenskt tidningspapper? - Bodén , Henny; Thiger, Evelina (2011)

(untitled)
According to Food and Agriculture Organization newsprint is defined as: Uncoated paper, unsized (or only slightly sized), containing at least 60 percent of mechanical wood pulp. The consumption of newsprint in Sweden was just over 798 000 tonnes in 2009, which represents approximately 90 kg per person. Although there are studies that predict a drastic reduction in newsprint consumption in the Western world, there seems to be a clear difference between forecasts for the future given by statistical analysis of newsprint consumption and forecasts given by experts in the industry. The former predict a continuing increase while the experts see a coming decrease in consumption. In this report, both demand and business strategies of newsprint in Sweden are studied. The study also presents a forecast of the future which is based on historical data and qualitative interviews. According to the regression analysis done in this research the consumption will increase with an increase in GDP. However, the qualitative interviews are pointing to another direction. Experts in the newsprint industry believe the increase in consumption of newsprint in Sweden will slow down over time and it might even decrease in total. This will probably largely depend on the development of information and communications technology such as Internet, e-readers and mobile phones. Business strategies for meeting the structural difference, that may appear in the future, varies from different parts of the industry. Newspapers are trying to create as attractive a product as possible regardless of whether it is in printed or digital form. Printing firms are trying to find additional customers for continued profitability. Paper mills strive to do as good a product as possible to compete and they try to sell more in the more profitable segments. The one similarity between the various parts in the industry is that everyone is trying to streamline their production.